Contexts of Faith: The Religious Foundation of Walter Ong's Literacy and Orality - Soukup, Paul A. (Journal of media and religion, 2006)
As priest and teacher, Walter Ong never separated his religious sensibility from his scholarship. Writing often about religious topics, he tells how he came to the fundamental insight (first articulated in Ramus, Method, and the Decay of Dialogue; Ong, 1958b) through his theological studies of the biblical Hebrew culture. Other aspects of his communication studies bear the mark of his religious vision, one sharing common elements with the theology of Pierre Teilhard de Chardin, whose writings he introduced to an American readership in the 1950s. Other religious influences on Ong's work range from his study of Thomistic philosophy and theology in the seminary to his literary studies of the religious poetry of Gerard Manley Hopkins.